Monsters in the mist - Brandt, Juliana (Sourcebooks Young Readers, 2022)
While his father is away on a teaching fellowship, Glennon and his family accept an invitation from his Uncle Job to stay with him on Isle Philippeaux on Lake Superior where he's the caretaker of a lighthouse. Soon after they arrive, Glennon realizes that all is not right with those who reside there. As he slowly uncovers the truth of the island's secrets, he comes to terms with trauma in his personal life.